2022
DOI: 10.3390/biomedicines10081800
|View full text |Cite
|
Sign up to set email alerts
|

Aβ and Tau Regulate Microglia Metabolism via Exosomes in Alzheimer’s Disease

Abstract: One of the most striking hallmarks shared by various neurodegenerative diseases, including Alzheimer’s disease (AD), is microglia-mediated neuroinflammation. The main pathological features of AD are extracellular amyloid-β (Aβ) plaques and intracellular tau-containing neurofibrillary tangles in the brain. Amyloid-β (Aβ) peptide and tau protein are the primary components of the plaques and tangles. The crosstalk between microglia and neurons helps maintain brain homeostasis, and the metabolic phenotype of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…45 The present study also confirmed the close relationships between M1 polarization of mi- the latter stage, such as IL-1β, soluble toxic Aβ peptides, caspase-1 and others. 47,48 The bioinformatics analysis in this study identified the critical role of exosome miR-124-3p in cognitive impairment, and we also observed the decreased miR-124-3p level in hippocampus after surgery, which provided a potential target for investigating the mechanism of cognitive impairment induced by postoperative pain.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…45 The present study also confirmed the close relationships between M1 polarization of mi- the latter stage, such as IL-1β, soluble toxic Aβ peptides, caspase-1 and others. 47,48 The bioinformatics analysis in this study identified the critical role of exosome miR-124-3p in cognitive impairment, and we also observed the decreased miR-124-3p level in hippocampus after surgery, which provided a potential target for investigating the mechanism of cognitive impairment induced by postoperative pain.…”
Section: Discussionmentioning
confidence: 63%
“…Some studies indicate microglial exosomes having both beneficial and detrimental effects for the development of Aβ abnormalities and neurodegeneration in neurodegenerative diseases 46 . In Alzheimer's disease, microglia activation acquired beneficial effects in the early stage by inducing phagocytosis and Aβ clearance with the help of microglial exosomes, while some substances in microglial exosomes damaged neurons in the latter stage, such as IL‐1β, soluble toxic Aβ peptides, caspase‐1 and others 47,48 . The bioinformatics analysis in this study identified the critical role of exosome miR‐124‐3p in cognitive impairment, and we also observed the decreased miR‐124‐3p level in hippocampus after surgery, which provided a potential target for investigating the mechanism of cognitive impairment induced by postoperative pain.…”
Section: Discussionmentioning
confidence: 72%
“…Various types of inflammasomes are also present in the cytosol of microglia, astrocytes, and neurons, where their activation contributes to the development and progression of neurodegenerative diseases in which inflammation is considered a common pathophysiological mechanism [ 1 , 247 , 248 ]. Neuroinflammation may involve exosomes that transport Aβ, tau, inflammatory factors, and other pathogenic substances between microglia, astrocytes, and neurons [ 249 , 250 ]. Exosome-inflammasome crosstalk has been documented: inflammasome activation can regulate exosomes release, and exosomes are an upstream regulator for inflammasome activation or inhibition [ 251 ].…”
Section: Hypotheses Of Alzheimer’s Diseasementioning
confidence: 99%
“…At the biochemical level, Alzheimer's disease is characterized by accumulation of insoluble forms of beta-amyloid (Aβ) and hyperphosphorylated tau protein (P-tau). There are ongoing discussions and debates on specific mechanisms of P-tau and Aβ pathogenicity, and various hypotheses have been presented, like neuronal cell death induced by abnormal P-tau fibrils in association with neuronal lesions and activation of glial cells caused by Aβ (Iwatsubo 2022), or neuroinflammation triggered by microglia metabolic reprogramming due to accumulation of Aβ and P-tau and their propagation to adjacent microglia through exosomes (Zhao et al 2022). Although it was supposed previously that Aβ and P-tau act independently, results of recent studies suggested that these two factors can interact and such interactions can contribute significantly to development of pathological changes, as summarized and discussed recently in detail by Busche and Hyman (2020).…”
Section: Alzheimer's Diseasementioning
confidence: 99%